Comparison Of Learning Results Using Time Token Learning Model With Talking Chips Assisted With Flashcard Media Students - Rahmasari, Yuni; Abdi, Abdul Wahab; Putri Afriyani, Mice (Seutia Hukamaa Cendekia, 2024)
The time token learning model is a type of learning characterized by time marks or time limits. Talking chips, namely learning carried out in small groups, each member brings several objects or signs that function to mark when they have an opinion by inserting a sign in one place. Flashcard media is visual learning media that contains words, images, or a combination thereof. This research compares geography learning outcomes using the Time Token learning model with the Talking Chips model assisted by Flashcard media for students at SMA Negeri 3 Kuala, Nagan Raya Regency. This research uses a quantitative approach with a Quasi-Experimental Design type of research. The samples in this study were class X IPS 1 students as experimental class I and class X IPS 2 students as experiment II. Research data collection uses tests. Analysis of this research data uses normality, homogeneity and hypothesis testing. Based on the results of the data analysis, it is known that the data is regular and homogeneous. Furthermore, the hypothesis test results obtained a t count value of 2.268 > t table 1.671. Based on the t count and t table values, it is known that t count > t table so that Ha is accepted. So, it is concluded that the learning outcomes of students taught using the Time Token learning model assisted by Flashcard media are better than the learning outcomes of students taught using the Talking Chips learning model assisted by Flashcard media in class X geography subjects at SMA Negeri 3 Kuala, Nagan Raya Regency.